Synthesis and Spectroscopic Characterization of Palladium(II) and Platinum(II) Complexes with Substituted Pyrazoles - ADHIKARI, NIMAIRATAN; SAHA (DECEASED), NITYANANDA (Asian Journal of Chemistry, 2010)
Pd(II) and Pt(II) complexes with substituted pyrazoles (1a-d) with various counter ions,X (X = Cl–, Br–, NO3–, SCN– and ClO4–) have been synthesised and characterized. Magnetic and electronic spectral data classify all the non-electrolyte mono-chelates as square planar species. IR data (down to 200 cm-1) point out that the two acid ligands (1a and 1b) and ester ligand (1c) exhibit neutral bidentate (NN) through two tertiary N atoms however the hydrazide one (1d) exercises neutral bidentate (NO) through pyrazolyl 2N and amidic oxygen, respectively. The counter ions are coordinated. A noticeable downfield shift of all most all of the protons in 1H NMR spectra has been immense helpful regarding binding sites.